The philosophy of outer space explorations, controversies, speculations - Garasic, Mirko Daniel; Di Paola, Marcello (Routledge research in anticipation and futures, 2024)
"This volume provides a rigorous philosophical investigation of the rationales, challenges, and promises of the coming Space Age. Over the past decade, space exploration has made significant and accelerating progress, and its potential has attracted growing attention from science, states, businesses, innovators, as well as the media and society more generally. However, philosophical theorizing concerning the premises, values, meanings, and impacts of space exploration is still in its infancy, and this potentially immense field of study is far from mainstream yet. This book advances outer space philosophy by integrating key scientific and societal debates sparked by recent developments in space research and activities with conceptual, existential, ethical, aesthetic, and political themes and concerns. It maps various regions of philosophical exploration, reflection, and speculation regarding humanity's present and future irradiation into outer space, to promote a broad, rich, and nuanced societal debate regarding this transformative enterprise, which is as stimulating as it can be disorienting. This book will be a fascinating philosophical and ethical exploration for academics, researchers and students interested in philosophy, space studies, science and technology studies, future studies, and sustainability"--